Descriptive Epidemiology of Human Thyroid Cancer: Experience From a Regional Registry and The “Volcanic Factor” - Malandrino, Pasqualino; Scollo, Claudia; Marturano, Ilenia; Russo, Marco; Tavarelli, Martina; Attard, Marco; Richiusa, Pierina; Violi, Maria Antonia; Dardanoni, Gabriella; Vigneri, Riccardo; Pellegriti, Gabriella (Frontiers in Endocrinology, 2013)
Thyroid cancer (TC), the most common endocrine tumor, has steadily increased worldwide due to the increase of the papillary histotype. The reasons for this spread have not been established. In addition to more sensitive thyroid nodule screening, the effect of environmental factors cannot be excluded. Because high incidences of TC were found in volcanic areas (Hawaii and Iceland), a volcanic environment may play a role in the pathogenesis of TC. In January 2002, the Regional Register for Thyroid Cancer was instituted in Sicily. With a population of approximately 5 million inhabitants with similar genetic and lifestyle features, the coexistence in Sicily of rural, urban, industrial, moderate-to-low iodine intake and volcanic areas provides a conducive setting for assessing the environmental influences on the etiology of TC. In Sicily, between 2002 and 2004, 1,950 new cases of TC were identified, with an age-standardized rate (world) ASR(w)=17.8/100000 in females and 3.7/100000 in males and a high female/male ratio (4.3:1.0). The incidence of TC was heterogeneous within Sicily. There were 2.3 times more cases in the Catania province (where most of the inhabitants live in the volcanic area of Mt. Etna): ASR(w)=31.7/105 in females and 6.4/105 in males vs 14.1 in females and 3.0 in males in the rest of Sicily. Multivariate analysis documented that residents in the volcanic area of Mt. Etna had a higher risk of TC, compared to the residents in urban, industrial and iodine deficient areas of Sicily. An abnormally high concentration of several chemicals was found in the drinking water of the Mt. Etna aquifer, which provides water to most of the residents in the Catania province. Our data suggest that environmental carcinogen(s) of volcanic origin may promote papillary TC. Additional analyses, including cancer biological and molecular features, will allow a better understanding of risk factors and etiopathogenetic mechanisms.